2011
DOI: 10.1038/nrc3093
|View full text |Cite
|
Sign up to set email alerts
|

The different roles of ER subtypes in cancer biology and therapy

Abstract: By eliciting distinct transcriptional responses, the oestrogen receptors (ERs) ERα and ERβ exert opposite effects on cellular processes that include proliferation, apoptosis and migration and that differentially influence the development and the progression of cancer. Perturbation of ER subtype-specific expression has been detected in various types of cancer, and the differences in the expression of ERs are correlated with the clinical outcome. The changes in the bioavailability of ERs in tumours, together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
546
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(581 citation statements)
references
References 164 publications
12
546
1
6
Order By: Relevance
“…Recent studies have indicated that the efficacy of endocrine therapy cannot be simply explained by the expression levels of ERα, but may be determined by the expression profiles of both ERα and ERβ, as well as their various splice variants (14,21,24,25). Furthermore, to understand the meaning of the demonstrated change in ERα-36 expression induced by BMP2 in breast cancer cells, additional research should be carried out to determine whether the ERα-36 reported in the present study is the same as that reported by Wang et al (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that the efficacy of endocrine therapy cannot be simply explained by the expression levels of ERα, but may be determined by the expression profiles of both ERα and ERβ, as well as their various splice variants (14,21,24,25). Furthermore, to understand the meaning of the demonstrated change in ERα-36 expression induced by BMP2 in breast cancer cells, additional research should be carried out to determine whether the ERα-36 reported in the present study is the same as that reported by Wang et al (21).…”
Section: Discussionmentioning
confidence: 99%
“…The ER signaling pathway plays a pivotal role in the development of different types of breast cancer (14). Two types of ERs have been identified, ERα and ERβ, both of which have many mRNA splice variants (15).…”
Section: Introductionmentioning
confidence: 99%
“…However, E2 effects in mammals include the regulation of growth and differentiation of several organs and tissues influencing the whole homeostasis maintenance in both male and female organisms (Thomas and Gustafsson 2011). Thus, Nar ability to interfere with ER activities raises some concerns on the putative unhealthy side effects of this flavonoid.…”
Section: Introductionmentioning
confidence: 99%
“…Although adult skeletal muscle is a stable tissue, it possesses the remarkable ability to rapidly recover and regenerate following injury (Thomas and Gustafsson 2011;Hawke and Garry 2001). In response to injury, undifferentiated satellite cells are activated from a quiescent state and proliferate as myoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Current data show that all cancer types are in some way related with the level of estrogen, estrogen receptors and aromatase or their polymorphisms [11][12][13][14]. Generally estrogen receptor (ER) alpha promotes proliferation, while ER beta supresses it but this is not the rule for all tissues; moreover, the ER status varies between neoplastic tissues.…”
Section: Introductionmentioning
confidence: 99%